Effect of Initial Cutting Age on Morphology, Biomass Production, Fiber Content, and In vitro Digestibility of Regrowth in Sunn Hemp (Crotalaria juncea L.) - Danil Herdi; Himmah Aliyatiddin; Yogi Sidik Prasojo; Nafiatul Umami; Bambang Suhartanto (Faculty of Animal Science, Universitas Gadjah Mada, 2026)
Sunn hemp (Crotalaria juncea L.) is a fast-growing leguminous plant widely used as a cover crop and green manure due to its high biomass yield and ability to improve soil fertility. However, its potential as a forage source remains underexplored, particularly during the regrowth phase, which is critical for sustainable feed production. This study was aimed to determine the effect of the first cutting age on morphology, biomass production, fiber content, and in vitro digestibility of regrowth in sunn hemp (Crotalaria juncea L.). A completely randomized design (CRD) with a unidirectional pattern was used, consisting of three cutting ages (6, 7, and 8 weeks), each with three replications. The observed variables included morphological characteristics (leaf length, leaf width, stem diameter, and plant height), biomass production, fiber content (NDF and ADF), and in vitro dry matter (DM) and organic matter (OM) digestibility. Data were analyzed using analysis of variance (ANOVA), and mean differences were tested with Duncan’s Multiple Range Test (DMRT). The results showed that cutting age had a significant effect (P < 0.05) on morphology, biomass production, and in vitro digestibility of DM and OM, but had no significant impact (P > 0.05) on fiber content of the first regrowth of sunn hemp. Cutting age of 6 weeks resulted in the highest values (P < 0.05) for leaf length (12.78 cm), leaf width (3.18 cm), plant height (133.76 cm), stem DM yield (2.77 tons/ha), leaf DM yield (2.39 tons/ha), stem DM digestibility (52.23%), leaf DM digestibility (82.45%), stem OM digestibility (47.26%), and leaf OM digestibility (77.61%). In conclusion, a cutting age of 6 weeks improved leaf length, leaf width, plant height, biomass production, and in vitro digestibility (DM and OM) of the first regrowth of sunn hemp.